Kitābah and Syahādah in Q.S. al-Baqarah [2]: 282: A Thematic Exegesis Study between Classical and Contemporary Perspectives and Its Relevance to Islamic Financial Practices in Indonesia - Budi Susetyo; Naqiyah Naqiyah; Fadhil G Lusaputra; Yuniarti Herwiwarni; Lustono Lustono; Irkham Auladi; Mohammed Elfadil Ahmed Bakhit (ZAD Al-Mufassirin, 2026)
This study is motivated by the increasing complexity of Islamic financial practices in Indonesia, which necessitates a more operational interpretation of Q.S. al-Baqarah [2]: 282, particularly regarding the concepts of kitābah and syahādah. The study aims to examine the construction of meaning of these two concepts in both classical and contemporary Qur’anic exegesis and to formulate their relevance to the principles of documentation, verification, and supervision in Islamic financial transactions. This research employs a qualitative library-based approach using a thematic (mawḍū‘ī) tafsir methodology through a comparative analysis of classical and contemporary tafsir works, academic literature, and Indonesian Islamic finance regulations. The findings reveal that kitābah has undergone a significant expansion in meaning, evolving from the recording of debt transactions into a broader principle of accountable documentation. Meanwhile, syahādah has developed from personal testimony into a mechanism of institutional verification and oversight. The novelty of this study lies in its use of kitābah and syahādah as analytical categories for linking the interpretive development of the āyah al-mudāyanah (the verse on financial transactions) with the contemporary needs of Islamic financial governance, rather than merely employing them as normative justifications for Islamic accounting practices. The study further argues that Q.S. al-Baqarah [2]: 282 can be positioned as an ethical and conceptual framework for strengthening transparency, accountability, and transactional justice within Islamic financial institutions.